2003
DOI: 10.1046/j.1525-142x.2003.03051.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of muscle‐related genes and two MyoD genes during amphioxus notochord development

Abstract: The notochord is one of the diagnostic features of the phylum Chordata. Despite the similarities in the early morphogenetic patterns of the notochords of various chordates, they are strikingly distinct from one another at the histological level. The amphioxus notochord is one example of an evolutionary novelty because it is made up of muscle cells. Our previous expressed sequence tag analysis, targeting messenger RNAs expressed in the adult amphioxus notochord, demonstrated that many muscle-related genes are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
4
26
0
1
Order By: Relevance
“…Three cell types of notochord cells that were denoted as NoD, NoM and NoV cells were observed, consistent with recent work that isolated and examined notochord-specific genes (Suzuki and Satoh, 2000;Urano et al, 2003). The NoD and NoV cells are probably precursors of the Müller's cells, which are found at the dorsal and ventral ends of the amphioxus adult notochord (Conklin, 1932;Ruppert, 1997b;Stach, 1999).…”
Section: Developmental Roles Of Bb1c and Bb2csupporting
confidence: 85%
See 3 more Smart Citations
“…Three cell types of notochord cells that were denoted as NoD, NoM and NoV cells were observed, consistent with recent work that isolated and examined notochord-specific genes (Suzuki and Satoh, 2000;Urano et al, 2003). The NoD and NoV cells are probably precursors of the Müller's cells, which are found at the dorsal and ventral ends of the amphioxus adult notochord (Conklin, 1932;Ruppert, 1997b;Stach, 1999).…”
Section: Developmental Roles Of Bb1c and Bb2csupporting
confidence: 85%
“…NoD cells are rather cuboidal in shape and are aligned in a single row just below the ventral midline of the nerve cord (Fig. 8E,G) (Urano et al, 2003). NoV cells are also aligned in a single row on the ventral side of the notochord tissue.…”
Section: Expression Of Bb1c and Bb2c During Notochord Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Ebf2 and Ebf3 are also expressed in the somites of chicken embryos, where they might be involved in skeletal development (El-Magd et al, 2013). In Amphioxus, the single homolog of Tbx1 is expressed in the developing branchial arches (Mahadevan et al, 2004), and although neither Ebf nor MyoD expression have been reported in branchial arches of Amphioxus, Tbx1, Ebf and MyoD homologues are all expressed in somitic mesoderm (Mahadevan et al, 2004;Mazet et al, 2004;Schubert et al, 2003;Urano et al, 2003). Taken together, these diverse observations point to deep evolutionary origins for the myogenic functions of Tbx1/10, COE and Mrf orthologs in bilaterians.…”
Section: Discussionmentioning
confidence: 99%